2011
DOI: 10.1103/physreva.83.062507
|View full text |Cite
|
Sign up to set email alerts
|

Casimir-Polder repulsion near edges: Wedge apex and a screen with an aperture

Abstract: Although repulsive effects have been predicted for quantum vacuum forces between bodies with nontrivial electromagnetic properties, such as between a perfect electric conductor and a perfect magnetic conductor, realistic repulsion seems difficult to achieve. Repulsion is possible if the medium between the bodies has a permittivity in value intermediate to those of the two bodies, but this may not be a useful configuration. Here, inspired by recent numerical work, we initiate analytic calculations of the Casimi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…Recently Parashar, Milton, Shajesh and Schaden carried out a detailed analysis clarifying the controversies involving different models of boundary condition and studied the Casimi-Polder interaction between an atom and a δ-function plate, among other things [4]. This important issue, of atoms and charges in interaction with material boundaries, has generated a renewed interest for both practical and theoretical reasons [5][6][7][8]. In this context Eberlein and Zietal devised a remarkable method [9], closely related to the electrostatic image method [10], to deal with a wide range of physical setups.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Parashar, Milton, Shajesh and Schaden carried out a detailed analysis clarifying the controversies involving different models of boundary condition and studied the Casimi-Polder interaction between an atom and a δ-function plate, among other things [4]. This important issue, of atoms and charges in interaction with material boundaries, has generated a renewed interest for both practical and theoretical reasons [5][6][7][8]. In this context Eberlein and Zietal devised a remarkable method [9], closely related to the electrostatic image method [10], to deal with a wide range of physical setups.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we observed that Casimir-Polder repulsion along a direction perpendicular to the symmetry axis of a semi-infinite planar conductor or a conducting wedge and an anisotropically polarizable atom could be achieved in the region close to the conductor [13]. Here we have shown that anisotropically polarizable atoms can also repel in this sense, provided they are sufficiently anisotropic, and have perpendicular principal axes.…”
Section: Discussionmentioning
confidence: 65%
“…The authors quite correctly point out that the statement in Ref. [13] that no repulsion is possible in the weak-coupling regime is erroneous. conductor, which just states that the tangential components of the electric field must vanish on the conductor.…”
Section: Repulsion Of An Atom By a Conducting Cylindermentioning
confidence: 89%
See 2 more Smart Citations